VETERINARIAN PERCEPTIONS OF CANINE GIARDIASIS AND COMMUNICATION ON ZOONOTIC POTENTIAL IN THE U.S. - Eppler, Megan (My University, 2021)
Certain Giardia assemblages are capable of infecting both canines and humans, especially children. Giardia, specifically G. duodenalis (also known as G. intestinalis and G. lamblia), is studied unequally across species, likely because Giardia infections are treated differently in veterinary and human medical perspectives. A plethora of studies and data exist for human cases of giardiasis; however, it is impossible to know if a human or canine is carrying a zoonotic assemblage of Giardia because molecular characterization is not routinely carried out in the clinical setting. However, a study from 2011 found that asymptomatic urban dogs in the Western United States were more frequently infected with zoonotic assemblages of Giardia than with canine specific assemblages of Giardia (Covacin et al., 2011). Additionally, little data has been collected on how veterinarians treat pets and advise owners on how to best prevent re-infection or zoonotic infection. Giardia has no approved canine treatments in the U.S., but veterinarians may utilize three different drug treatments to help control the infection: metronidazole, fenbendazole, or febantel. It is important to understand veterinarian perceptions and practices for treating Giardia within the context of One Health. The goal of this cross-sectional study was to determine what types of treatments veterinarians are using, whether they are educating the pet owners on zoonotic potential from different assemblages of Giardia, and whether they are advising control measures to prevent environmental contamination by Giardia (e.g., washing bedding and bathing pets).
Keywords: giardia; zoonotic; veterinarians; treatment; survey; dogs